Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

Sequential model-based design of experiments for a heat-integrated biomass downdraft gasifier - Houda M. Haidar; James W. Butler; Peter Gogolek; Kimberley B. McAuley (Bioresource Technology, 2025)

Modeling of a heat-integrated biomass downdraft gasifier: Influence of feed moisture and air flow - Houda M. Haidar; James W. Butler; Samira Lotfi; Anh-Duong Dieu Vo; Peter Gogolek; Kimberley McAuley (Biomass and Bioenergy, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Validation of load based testing methodology for residential air conditioners and heat pumps - Parveen Dhillon; Drew Welch; Brian Butler; W. Travis Horton; James E. Braun (Energy and Buildings, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Shear stress and sediment resuspension in relation to submersed macrophyte biomass - William F. James; John W. Barko; Malcolm G. Butler (Hydrobiologia, 2004)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)